2020
DOI: 10.1016/j.lanwpc.2020.100001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid whole-exome sequencing facilitates precision medicine in paediatric rare disease patients and reduces healthcare costs

Abstract: Background: Rapid whole-exome sequencing (rWES) offers the potential for early diagnosis-predicated precision medicine. Previous evidence focused predominantly on infants from the intensive care unit (ICU). This study sought to examine the diagnostic and clinical utility, and the economic impact on clinical management of rWES in patients beyond infancy and ICU setting. Methods: rWES was performed on a prospective cohort of patients with suspected monogenic disorder referred from territory-wide paediatric ICUs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…As highlighted, it is possible to work before the pharmaceutical life cycle starts-by increasing the health status/ wellness of humans (working in the downstream of health) and the quality of the environment (here, also combating climate change should be added). The actions preventing the diseases, such as healthy lifestyle and early diagnosis, have measurable benefits for society and lower the cost of healthcare (Chung et al 2020;de Boer et al 2020;Laroche et al 2020). The cost of actions is hard to determine, as well as the environmental profits, but generally, working in the downstream of the life cycle is connected with higher costs.…”
Section: Actions Prioritizationmentioning
confidence: 99%
“…As highlighted, it is possible to work before the pharmaceutical life cycle starts-by increasing the health status/ wellness of humans (working in the downstream of health) and the quality of the environment (here, also combating climate change should be added). The actions preventing the diseases, such as healthy lifestyle and early diagnosis, have measurable benefits for society and lower the cost of healthcare (Chung et al 2020;de Boer et al 2020;Laroche et al 2020). The cost of actions is hard to determine, as well as the environmental profits, but generally, working in the downstream of the life cycle is connected with higher costs.…”
Section: Actions Prioritizationmentioning
confidence: 99%
“…Soden et al provide the mean costs of prior negative testing in non-acute individuals (inflated and currency converted value: 17,785.18€). Chung et al 43 , Monroe et al 42 and Vrijenhoek et al 22 calculated the cost savings per individual resulting from avoidable medical examinations due to early ES implementation (inflated and currency converted values: 110.63€; 3,277.66€ and 5,090.39€). In some of these publications the costs of potentially unnecessary diagnostics even exceeded costs for ES.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid WES can often provide results within 2 weeks and therefore may impact clinical decision‐making for a patient hospitalized with ALF 23 . Chung et al 24 reported that the median turnaround for rapid WES was 11 days and changed clinical management in 88% of patients with suspected monogenic disorders. In our patient, the results of rapid WES were reported within 5 days, which allowed us to quickly make the diagnosis of APS‐1.…”
Section: Discussionmentioning
confidence: 99%